Pathological role of methionine in the initiation and progression of biliary atresia - Jiachen, Zheng; Paul Kwong Hang, Tam; Kenneth Kak Yuen, Wong; Vincent Chi Hang, Lui (Frontiers in Pediatrics, 2023)
Methionine is an essential amino acid, and its excessive dietary intake and/or metabolism disturbances could lead to accumulation/depletion of hepatic Met and some of the key intermediates of these pathways, which would interfere the normal liver function and associated with liver diseases.Biliary atresia (BA) is a life-threatening inflammatory fibrosclerosing disease of the intrahepatic and extrahepatic biliary system, and a major cause of obstructive neonatal choleastasis with a rapid course of liver failure. But its pathogenesis is still not fully known. Previous studies reported elevated Met level in obstructive cholestasis patients, suggesting a potential link between Met and BA. This paper reviews the Met metabolism in normal condition, and its dysregulation under abnormal conditions. The possible causes of hypermethioninemia, and its connection to BA pathogenesis: Abnormal hepatic level of Met could lead to a perturbation of redox homeostasis and mitochondrial functions of hepatocytes, enhancemenet of viral infectivity, dysregulation of innate and adaptative immune cells in response to infection/damage of liver contributing to the initiation/progression for BA.